ANALYSIS OF DEFECT RATE IMPROVEMENT IN THE SMARTPHONE ASSEMBLY INDUSTRY USING SPC AND DMAIC APPROACH - Rahmawati, Nurfitri; Hasbullah, Hasbullah (AIBPM Publisher, 2023)
In the current era, business is experiencing very rapid development, one of which is the smartphone assembly industry. With the high demand for smartphones from the public, companies will compete to be able to produce quality smartphones with predetermined standards and specifications. Quality control is needed by the company to maintain the products it produces. It is known that the company's production target is 99.50%. However, this target has never been achieved due to a large number of defect smartphones. Based on calculations using SPC and DMAIC, it is known that most defects are found in production line 1 with the type of smartphone product type B and the type of defect, namely LTE test fail. For this reason, the research that will be carried out in this study focuses on the LTE test fail defect. The cause of main problem in this research is machine error. Before the repair, the %p value was 2.6% and after the repair was carried out by restarting the machine every 2 hours, the %p value was 1%.